Culture results on chest tube thoracostomy water-sealed drainage in patients with pneumothorax at Sanglah General Hospital, Bali-Indonesia - Putu Bagus Anggaraditya; Arland Chandra (DiscoverSys Inc., 2019)
Introduction: Thoracic trauma is one type of trauma with a high incidence that causes morbidity and mortality after head trauma and extremity. The act of installing a thoracostomy has become one of the standard management of thoracic injury. Infection is a complication that can occur during treatment. This study aimed to provide an overview of the results of thoracostomy tube water-sealed drainage (WSD) culture in pneumothorax patients at Sanglah Hospital.Method: The study design used a cross sectional descriptive method. The subjects of the study were blunt thoracic trauma patients with pneumothorax who came to the emergency department of Sanglah Hospital to indicate the installation of a thoracostomy hose during the period January to December 2018.Results: From 40 study samples there were 32 subjects with positive culture results, then from all subjects with positive culture results found 10 people (25%) with culture results of staphylococcal aureus bacteria, based on rib fractures more samples with rib fractures less than two bones ( 62.5%), based on the duration of WSD installation there were more samples with the duration of WSD installation more than 7 days (75%).Conclusion: The high positive culture results which are dominated by pyogenic skin bacteria, namely Stapylokokus aureus is a challenge for surgeons in managing the complications of tube thoracostomy (TT) installation in patients with pneumothorax.